Answer:
x = - 2
y = - 4
Explanation:
The given equations are:
![$ 4x - 3y = 4 \hspace{10mm} \hdots (1) $](https://img.qammunity.org/2021/formulas/mathematics/middle-school/zpx11q3t1ss34ozo76i5zsrywft35e30ka.png)
![$ x - y = 2 \hspace{12mm} \hdots (2) $](https://img.qammunity.org/2021/formulas/mathematics/middle-school/leckrrfwl3xof5nreevzrp9tfv0z606z1c.png)
To solve this system of equations, we eliminate one variable.
Let us eliminate the variable 'x' here.
To do that multiply Equation (2) by 4.
⇒ 4x - 4y = 8 . . . (3)
The co - effecients of x in both the equations are now same. Subtract the two equations.
(1) - (3) = -3y - (-4y) = 4 - 8
⇒ - 3y + 4y = - 4
⇒ y = - 4
Substituting the value of 'y' in Equation (2) we get:
x - (-4) = 2
⇒ x + 4 = 2
⇒ x = - 2 which is the required answer.
Hence (x, y) = (-2, - 4) is the solution to the above system of equations.